Structure of self-assembled monolayers of partially fluorinated alkanethiols with a fluorocarbon part of variable length on gold substrate - Lu, Hao; Zeysing, Daniela; Kind, Martin; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2013)
A series of self-assembled monolayers (SAMs) formed on Au(111) from partially fluorinated alkanethiols (PFAT) with variable length of the fluorocarbon chain, viz. F(CF2)n(CH2)11SH (FnH11SH, n = 6, 8, and 10), was studied by high resolution X-ray photoelectron spectroscopy, infrared reflection absorption spectroscopy, and near edge X-ray absorption fine structure spectroscopy. The SAMs were found to be highly ordered and densely packed. The packing density was governed by the bulky fluorocarbon segments which adopted a helical conformation typical of this entity. With decreasing length of the fluorocarbon segment, progressive deterioration of the orientational order accompanied by a slight decrease in the packing density was observed in the fluorocarbon part of the FnH11SH SAMs. The conformation of the fluorocarbon segment was persistent through the series, with probably only a minor deterioration for n = 8 and 6. The hydrocarbon segments of the monolayers were, however, unaffected by the deterioration of the orientational order in the fluorocarbon part. They persistently exhibited all trans planar conformation, typical of densely packed assemblies of these moieties, while their orientation, given by the characteristic tilt and twist angles, mimicked that of the nonsubstituted alkanethiolate SAMs on Au(111). This behavior is explained by the effect of the bending potential which predefines the orientation of the hydrocarbon segments even if they are separated beyond the equilibrium spacing by the bulky fluorocarbon moieties.